Exploiting green analytical procedures for acidity and iron assays employing flow analysis with simple natural reagent extracts - Kate Grudpan (2018)
Green analytical methods employing flow analysis with simple natural reagent extracts have been exploited. Various formats of flow based analysis systems including a single line FIA, a simple lab on chip with webcam camera detector, and a newly developed simple lab on chip system with reflective absorption detection and the simple extracts from some available local plants including butterfly pea flower, orchid flower, and beet root were investigated and shown to be useful as alternative self indicator reagents for acidity assay. Various tea drinks were explored to be used for chromogenic reagents in iron determination. The benefit of a flow based system, which allows standards and samples to go through the analysis process in exactly the same conditions, makes it possible to employ simple natural extracts with minimal or no pretreatment or purification. The combinations of non-synthetic natural reagents with minimal processed extracts and the low volume requirement flow based systems create some unique green chemical analyses. © 2011 Elsevier B.V. All rights reserved.